The Phenomenon of "Badapu" Tradition with Nutritional Status in Postpartum Mothers in West Aceh - Zakiyuddin, Zakiyuddin; Reynaldi, Fitrah (International Journal of Engineering, Science and Information Technology, 2021)
Cultural practices negatively affect public health behavior, making it more likely to have an infection. In Aceh there is a tradition applied to post-partum mothers called Madeung, which is a tradition carried out by women after giving birth for 44 days with a variety of applicable provisions. The purpose of this study was to determine the nutritional status of postpartum mothers based on the phenomenon of carrying out the tradition of "Badapu" as an effort to improve nutrition for postpartum mothers in West Aceh. This type of research is explanatory survey or explanation aimed at studying the patterns of consumption of traditional food "Badapu" in West Aceh (quantitative) and people's perceptions of traditional food Badapu (qualitative). The planned design is one group before and after intervention design, or one group pre and post test design. The results obtained illustrate the pattern of food consumption in postpartum mothers who carry out the tradition of Badapu, which varies slightly and is almost the same every day with the main menu of rice, eggs and fried fish. All postpartum mothers (100%) consume rice as a food source of carbohydrate as the biggest energy contributor. At least puerperal mothers who eat snacks because there are restrictions on being able to consume these foods. The existence of restrictions on postpartum mothers who carry out the tradition of Badapu to consume several types of food ingredients that contain water, which is generally found in vegetables and fruits.